Online Learning Activities and Social Styles of Online Learners in General English Course: A Survey in Two Classes in a Private Higher Educational Institution in Bandung Indonesia - Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This paper is a report of a survey on identifying the most preferred online learning activities in an online learning platform and types of leaner styles taking General English Course as an obligatory course in two classes in a private higher educational institution. The aim of this study is to identify the most preferred online activities and the tendency of social learners of online learner in online learning platform. The data employed in this study were gained by distributing a survey to sixty-four online learners and categorized them into online learning activities and the social learning styles from Grasha-Riechman Student Learning Style Scales. The results indicate that the most preferred online learning activities are doing practices or exercises, conducting virtual meeting and watching videos and their social learning styles in online learning tend to be more dependent, collaborative and participative.